(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
In the context of contemporary urbanization processes, climate change, and the growing demand for high-quality and affordable housing, European cities are facing the need to transition toward sustainable and integrated models of spatial development. One of the key forms of such transformation is multifunctional residential complexes that combine housing, public spaces, service facilities, and elements of green infrastructure. The aim of this study is to conduct a comprehensive analysis of the architectural and urban planning foundations underlying the formation of contemporary residential complexes and multifunctional residential ensembles in the city of Karlsruhe as key elements of a sustainable urban environment, as well as to determine their role in the transformation of the spatial structure, functional organization, and quality of the residential environment within the framework of compact and integrated urban development. The study applies a comprehensive architectural and urban-planning approach, including an analysis of the urban structure of Karlsruhe, a typological study of residential and multifunctional complexes, and an examination of key projects—BadenCarré, Rintheimer Feld, and Ettlinger Tor. Particular attention is paid to issues of multifunctionality, the organization of public spaces, the integration of social infrastructure, and the application of sustainable development principles. As a result of the study, it has been established that contemporary residential complexes in Karlsruhe form a qualitatively new type of organization of urban residential development based on high density, multifunctionality, and orientation toward public transport. Such complexes contribute to reducing transport dependency, improving the quality of the residential environment, and enhancing the resilience of the urban structure. The findings confirm that the experience of Karlsruhe can be regarded as a promising model for the transformation of residential development in European and post-socialist cities.